Taxonomic revision of south-eastern Australian giant burrowing frogs (Anura: Limnodynastidae: Heleioporus Gray) - Mahony, Michael J.; Penman, Trent; Bertozzi, Terry; Lemckert, Frank; Bilney, Rohan; Donnellan, Stephen C. (Zootaxa, 2021)
The rarely encountered giant burrowing frog, Heleioporus australiacus, is distributed widely in a variety of sclerophyll forest habitats east of the Great Dividing Range in south-eastern Australia. Analyses of variation in nucleotide sequences of the mitochondrial ND4 gene and thousands of nuclear gene SNPs revealed the presence of two deeply divergent lineages. Multivariate morphological comparisons show the two lineages differ in body proportions with > 91% of individuals being correctly classified in DFA. The two lineages differ in the number and size of spots on the lateral surfaces and the degree by which the cloaca is surrounded by colour patches. The mating calls are significantly different in number of pulses in the note. The presence of a F2 hybrid in the area where the distribution of the two taxa come into closest proximity leads us to assign subspecies status to the lineages, as we have not been able to assess the extent of potential genetic introgression. In our sampling, the F2 hybrid sample sits within an otherwise unsampled gap of 90km between the distributions of the two lineages. The nominate northern sub-species is restricted to the Sydney Basin bioregion, while the newly recognised southern subspecies occurs from south of the Kangaroo Valley in the mid-southern coast of New South Wales to near Walhalla in central Gippsland in Victoria. The habitat of the two subspecies is remarkably similar. Adults spend large portions of their lives on the forest floor where they forage and burrow in a variety of vegetation communities. The southern subspecies occurs most commonly in dry sclerophyll forests with an open understory in the south and in open forest and heath communities with a dense understory in the north of its distribution. The northern subspecies is also found in dry open forests and heaths in association with eroded sandstone landscapes in the Sydney Basin bioregion. Males of both taxa call from both constructed burrows and open positions on small streams, differing from the five Western Australian species of Heleioporus where males call only from constructed burrows. Using the IUCN Red List process, we found that the extent of occupancy and area of occupancy along with evidence of decline for both subspecies are consistent with the criteria for Endangered (A2(c)B2(a)(b)).